Comparison of fungal diversity in different areas of soil use in the Pampa Biome - Rodrigues, Douglas Henrique Giovanella; Müller, Thais; Rempel, Claudete; Silva, Guilherme Liberato da; Heidrich, Daiane; Maciel, Mônica Jachetti (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
In southern Brazil, together with Argentina and Uruguay, is located the Pampa Biome. The fungal diversity present in this place can be affected by soil exploitation, which end up, consequently, influencing other biological communities. The objective of this study was to compare the fungal diversity in different land use areas in the Pampa Biome. For that, soil collections were carried out in the city of Pantano Grande, located in Rio Grande do Sul. Three different land use areas were sampled: native, pasture and forestry areas. Soil fungi were isolated using the decimal dilution technique. Identification occurred through observations of macro and microscopic characteristics. Through statistics methods, the diversity of fungi was analyzed and the fungal community was compared between the sampled areas. A total of 265 individuals distributed in nine taxonomic types were isolated. The three areas had four taxa in common (Aspergillus niger, Aspergillus sp., Trichoderma sp. and Fusarium sp.), while the areas used for pasture were the only ones to present exclusivity in the presence of a taxon (Verticillium sp.). With this, it was possible to conclude that the areas used for pasture have the highest fungal biodiversity among the studied areas; however, statistically, the fungal richness between the different types of land use did not present differences.